2002
DOI: 10.1021/jo025635q
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Analysis of Furanose Rings with PSEUROT:  Parametrization for Rings Possessing the Arabino, Lyxo, Ribo, and Xylo Stereochemistry and Application to Arabinofuranosides

Abstract: The solution conformation of a furanose ring can be assessed through PSEUROT analysis of three-bond (1)H-(1)H coupling constants ((3)J(HH)) of the ring hydrogens. For each coupling constant, PSEUROT requires two parameters, A and B, which are used to translate the H[bond]C[bond]C[bond]H dihedral angle predicted from the (3)J(HH) into an endocyclic torsion angle from which the identity of the conformers can be determined. In this paper, we have used density functional theory methods to generate a family of enve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 37 publications
5
56
0
1
Order By: Relevance
“…Thus, the relationship between the five torsion angles (Fig. 1) determined the phase (P) and the amplitude of the sugar unit 21 (Table 5). It has been shown that the sugar in (5 0 R)cdA adopts an unusual W-west conformation, 0 T 1 .…”
Section: Determination Of the Sugar Moiety Conformation By 2d Noesy Ementioning
confidence: 99%
“…Thus, the relationship between the five torsion angles (Fig. 1) determined the phase (P) and the amplitude of the sugar unit 21 (Table 5). It has been shown that the sugar in (5 0 R)cdA adopts an unusual W-west conformation, 0 T 1 .…”
Section: Determination Of the Sugar Moiety Conformation By 2d Noesy Ementioning
confidence: 99%
“…Although intriguing, there are scant data to support the flexible scaffold hypothesis. As part of a program dedicated to understanding the conformation of mycobacterial AG (and LAM), we have carried out a series of NMR studies on the arabinofuranose-containing oligosaccharides 13,14 and coupled these experimental studies with high-level ab initio and density functional theory calculations on methyl α-D-arabinofuranoside (1, Figure 1) 15,16 and related analogs. [17][18][19][20] Given their inherent flexibility, the conformational analysis of furanosides is more complicated than comparable studies with pyranosides as more than one ring conformer must be considered.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] Having studied the conformation of 1 using both experimental and high-level computational methods, we are interested in looking at larger oligomers of D-arabinofuranose, for which we have NMR data. 13,14 However, given the size of these molecules, their treatment with ab initio or density functional theory methods is of limited practicality. Thus, we have begun to investigate the use of force field models to probe the conformation of these oligosaccharides.…”
Section: Introductionmentioning
confidence: 99%
“…The experimentally measured ribose proton coupling constants of compounds 1 – 6 (Figure 1) obtained from DAISYSIM fitting were used as input for PSEUROT 6.2 and a similar Matlab program (Frank A A M De Leeuw & Altona, 1983; Houseknecht et al, 2002; Rosemeyer et al, 1997; Watts et al, 2006). The optimized conformations as well as the equilibrium between them, expressed as %S-conformer, were comparable for each program and agreed with published results (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The refined coupling constants were used as the input into PSEUROT 6.2 to calculate the pseudorotation parameters (Frank A A M De Leeuw & Altona, 1983; Houseknecht, Altona, Hadad, & Lowary, 2002; Rosemeyer et al, 1997; Watts, Sadalapure, Choubdar, Pinto, & Damha, 2006). In addition, a Matlab based pseudorotation GUI was used for substantiation (Hendrickx & Martins, 2008).…”
Section: Methodsmentioning
confidence: 99%